Performance evaluation of embedded acoustic emission sensors in a glass fibre composite under mechanical loading - Ghadarah, Noor Salam; Ayre, David (Elsevier, 2024)
Fully embedding acoustic emission (AE) sensors in a composite is postulated to increase the sensor’s sensitivity. The increased sensitivity will enable the sensor to detect subtle structural changes and lower the number of sensors required for monitoring. However, researchers have differed on whether the sensitivity increases or not. To robustly investigate the fully embedded AE sensor’s sensitivity, the surface and fully embedded AE sensors are placed on the same specimen, away from the high-stress region and compared based on the same hit. Two mechanical testing methods are used: three-point bend and double cantilever beam (DCB) mode I. Three sensors are embedded: lead zirconate titanate (PZT), gold-plated polyvinylidene difluoride (PVDF), silver-ink PVDF. The DCB mode I method showed that the sensitivity of the surface embedded sensor was generally better or equal to the fully embedded sensor. However, the three-point bend method showed similar sensitivity with both surface and fully embedded sensors. The results indicate that the fully embedded sensor’s sensitivity is based on the frequency of the AE event and, therefore, the failure type. The aim of the study is to analyse the sensitivity of the surface-embedded and fully embedded sensors concerning surface-originating and subsurface-originating cracks.
Keywords: AE; PZT; PVDF; Integration; Sensitivity